Religious Beliefs on the Use of Family Planning Methods as Expressed by Married Adults in Ilorin Metropolis, Kwara State - Odebode, Aminat Adeola; James, Joke Felicia; Ijaodola, Tawakalitu Kike (JHE (Journal of Health Education), 2020)
Background: This research was carried out to investigate the influence of religious beliefs on the use of family planning methods as expressed by married adults in Ilorin metropolis, Kwara State, Nigeria. In the study, variables such as gender, religion, and highest educational qualifications were examined for their influence on the respondents’ views. Methods: Descriptive research design was adopted for the study. A total of 240 married adults participated in the study. An instrument titled Religious Beliefs and Family Planning Use Questionnaire (RBFPUQ) was used to gather data for the study. The validity of RBFPUQ was conducted by giving the instruments to a team of experts in the University of Ilorin, Nigeria Results: The study revealed that religious beliefs have no influence on the use of family planning methods. The study also showed that there was no significant difference in the respondents’ views based on gender and educational qualification but there was a significant difference based on religion. Conclusions: It was recommended that counselors and health workers should liaise with religious leaders to organize seminars and workshops concerning reproductive issues for married adults in Kwara State. This should be regularly conducted for enlightenment as this will enable married adults to further put various family planning methods that are within their reach to use.